Participation in physical activity for adolescents with disabilities: Parents' perspective - Dena Widyawan (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
This study is to describe the role of parents in promoting the physical activity of adolescents with disabilities and to describe their perceptions of participation. This study used a qualitative descriptive design. Sample procedure using convenience sampling. A total of 28 parents of youth with disabilities aged twelve - sixteen years. Data analysis used content analysis, with the development of inductive categories using Nvivo 11 software. For eight weeks, data were collected from January to February 2020. All samples explained how many challenges involved participating in physical activities of adolescents with disabilities. After all, parents would like to see their children participating in more physical activity, but consider the promotion of physical activity to be a very demanding task that is difficult to handle alone. The finding is that the promotion of physical activity habits among adolescents with disabilities needs to be prioritized, that the support provided needs to be tailored to the needs of adolescents and their families as well as collaborative efforts and support from all partiesKeywords: adolescent, physical activity, parents, persons with disabilities